Accounting for spatially heterogeneous conditions in local‐scale surveillance strategies: case study of the biosecurity insect pest, grape phylloxera (Daktulosphaira vitifoliae (Fitch)). Issue 12 (28th June 2018) - Triska, Maggie D; Powell, Kevin S; Collins, Cassandra; Pearce, Inca; Renton, Michael
Abstract: BACKGROUND: Surveillance strategies are often standardized and completed on grid patterns to detect pest incursions quickly; however, it may be possible to improve surveillance through more targeted observation that accounts for landscape heterogeneity, dispersal and the habitat requirements of the invading organism. We simulated pest spread at a local scale, using grape phylloxera ( Daktulosphaira vitifoliae (Fitch)) as a case study, and assessed the influence of incorporating spatial heterogeneity into surveillance compared with current, standard surveillance strategies. RESULTS: Time to detection and spread within and beyond the vineyard were reduced by conducting surveys that target sampling effort in soil that is highly suitable for the invading pest in comparison with standard surveillance strategies. However, these outcomes were dependent on the virulence level of phylloxera because phylloxera is a complex pest with multiple genotypes that influence spread and detectability. CONCLUSION: Targeting surveillance strategies based on local‐scale spatial heterogeneity can decrease the time to detection without increasing the survey cost, and surveillance that targets highly suitable soil is the most efficient strategy for detecting new incursions. In addition, combining targeted surveillance strategies with buffer zones and hygiene procedures, and updating surveillance strategies as additional species information becomes available, will further decrease the risk of pest spread. © 2018 Society of Chemical Industry Abstract : We designed a spread model to assess standard and targeted surveillance strategies. Overall, targeted strategies that incorporate local‐scale spatial heterogeneity may decrease the time to detection without increasing surveillance cost.